Contribution of specific pathogens to bloodstream infection mortality in neutropenic patients with hematologic malignancies: Results from a multicentric surveillance cohort study. Issue 6 (1st November 2019) - Kern, Winfried V.; Roth, Jan A.; Bertz, Hartmut; Götting, Tim; Dettenkofer, Markus; Widmer, Andreas F.; Theilacker, Christian; ,
Abstract: Bloodstream infection (BSI) remains a serious complication in patients with hematologic malignancies and neutropenia. The risk factors for mortality after BSI and the contributions of BSI pathogens to mortality remain incompletely understood. We evaluated first BSI among adult neutropenic patients undergoing high‐dose chemotherapy for hematologic malignancies in the setting of (a) an early disease stage of autologous (auto‐HSCT) or allogeneic (allo‐HSCT) hematopoietic stem cell transplantation or (b) for acute leukemia. Risk factors for intensive care admission and all‐cause mortality were analyzed by multivariable logistic regression 7 and 30 days after onset of the first BSI in the first neutropenic episode. Between 2002 and 2015, 9080 patients met the study inclusion criteria, and 1424 (16%) developed BSIs, most of them during the first week of neutropenia. Mortality during neutropenia within 7 days and 30 days after BSI onset was 2.5% and 5.1%, respectively, and differed considerably between BSI pathogens. Both 7‐day and 30‐day mortalities were highest for Pseudomonas aeruginosa BSI (16.7% and 26.7%, respectively) and lowest for BSI due to coagulase‐negative Staphylococcus spp. (CoNS) and Streptococcus spp. BSI pathogens were independently associated with 7‐day mortality included P aeruginosa, Klebsiella spp., Enterobacter spp., Serratia spp., and enterococci. Only gram‐negative BSI and candidemia were associated with admission to intensive care within 7 days after BSI onset. BSI caused by P aeruginosa continues to carry a particularly poor prognosis in neutropenic patients. The unexpected association between enterococcal BSI and increased mortality needs further study.